INCREASING POPULATION INCOMES IN THE REGION BASED ON THE PRINCIPLES OF THE GREEN ECONOMY - Nomazov, Bakhrom Bobomuradovich (THE INNOVATION ECONOMY, 2026)
This article scientifically examines the economic mechanisms for increasing population incomes in the regions of the Republic of Uzbekistan based on the principles of the green economy. According to data from the Statistics Agency, in 2024 the total income of Uzbekistan’s population amounted to 896.3 trillion soums, with a real growth rate of 8.1%; by the end of 2025, incomes grew by 9.2% in real terms, and the average monthly per capita income reached 2.5 million soums. However, interregional income inequality is increasing: the gap between Tashkent city and the Republic of Karakalpakstan reached 3.51 times by the end of the third quarter of 2025. The principles of the green economy—renewable energy, the “Solar Household” program, green tariffs, resource efficiency, and environmental certification—are analyzed as effective instruments for reducing regional income inequality and ensuring sustainable growth of population incomes.